2013
DOI: 10.1007/s10661-013-3498-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the bacterial load and antibiotic susceptibility of dental units

Abstract: The aim of this study was to evaluate the bacterial contamination level and to determine the antibiotic susceptibility of the isolated bacteria from dental unit waterlines (DUWLs) in Istanbul. Bacterial quality of DUWLs is very important, as patients and dental staff are regularly exposed to water and aerosols generated by the unit. If opportunistic pathogens such as Staphylococcus aureus, Pseudomonas aeruginosa, and Legionella pneumophila are present in DUWLs, patient and dental staff can be infected. One hun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
2
10
0
1
Order By: Relevance
“…Dentists, like other healthcare professionals, are ethically obliged to provide patients with a safe and clean clinical environment including the water supplied by DUs. This piece of work has confirmed the results of earlier research, 7,12 which reported that the microbiological quality of water emerging from DUs did not conform to the accepted guidelines for potable water. In the present study, 88.3% of the examined DUWL output water samples failed to meet the Egyptian standards for HPC bacteria.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Dentists, like other healthcare professionals, are ethically obliged to provide patients with a safe and clean clinical environment including the water supplied by DUs. This piece of work has confirmed the results of earlier research, 7,12 which reported that the microbiological quality of water emerging from DUs did not conform to the accepted guidelines for potable water. In the present study, 88.3% of the examined DUWL output water samples failed to meet the Egyptian standards for HPC bacteria.…”
Section: Discussionsupporting
confidence: 87%
“…This seems to be consistent with the results obtained by other authors, 1,14 who attributed the higher contamination of high-speed handpiece to their In accordance with the results reported by Turetgen et al, 15 the current study found that DUWLs output water was more contaminated than the source water. Some researchers 7,12 have attributed the higher level of contamination in the output water compared to the inlet water to the release of bacteria from biofilms lining the DUWLs; an explanation that can apply to the results of the current study too. The decrease in the mean HPC values after clinical activity observed in this study has also been previously reported; 16,17 it can be attributed to the continued flushing of the waterlines during and between treatment sessions which can decrease the count in the midday samples.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…in any DUWLs, they were able to detect L. pneumophilia in one of the tap water samples using the SCT. In another study regarding bacterial load of dental units conducted by Güngör et al in İstanbul, Turkey [21], Legionella was not detected in any water and aerosol samples, but Pseudomonas aeruginosa was isolated in three DUWLs. Furthermore, Pseudomonas and Staphylococcus also were found in water and aerosol samples.…”
Section: Discussion Of Resultsmentioning
confidence: 87%